Interrogating the Impact of Land Use/Land Cover Dynamics in Mbarara City in Southwestern Uganda - Nuwagira, Upton; Igga Yasin; Nasasira, Perfect (East African Journal of Environment and Natural Resources, 2023)
While some research has been conducted in sub–Saharan Africa on the alien invasive Parthenium hysterophorus, little work has assessed whether it is poses negative impact on native forages. A field survey was carried out to study the dominant co–existing plant species, and its impact on plant abundance, species, and native forage cover. We found that non–natives were the dominant co–existing plants with P. hysterophorus compared to natives. Plant species (r = -0.889, P = 0.043) and abundance (r = -0.968, P = 0.007) decreased with increasing invasive percent cover. Moreover, native forage plant (Brachiaria reptans; r = -0.922, P = 0.026), Cynodon dactylon; r = -0.972, P = 0.006, Digitaria milanjiana; r = -0.938, P = 0.018, and Indigofera spicata; r = -0.977, P = 0.004) percent cover decreased with increasing invasive percent cover. The study concludes that P. hysterophorus negatively affects plant diversity, and thus, should controlled.